Relationship Between Household Food Security And Nutritional Status Of Toddlers In Flood-Prone Areas Of Surakarta - Rafifah, Hasna; Ria Rakhma, Luluk; Kurnia, Pramudya (JURNAL ILMIAH AGRINECA, 2025)
Flooding poses numerous negative consequences, particularly for the food security of households in areas prone to flooding. The nutritional health of children under five is directly affected by household food security, highlighting the strong connection between the two. The study was carried out in flood-prone areas within the Pasar Kliwon District of Surakarta, specifically in the villages of Sangkrah and Semanggi. This observational research used a proportional random sampling method to select participants. The respondents were heads of households or mothers, along with their children under five years of age. The collected data includes socio-economic factors such as income, gathered through interviews using a questionnaire. The HFIAS questionnaire was employed to assess household food security, while nutritional status was evaluated through anthropometric measurements. Z-scores were calculated using the WHO-Antro software, with WAZ and BAZ indicators serving to assess nutritional status. Statistical analyses, including the Fisher Exact test and Chi-Square test, were applied to examine correlations between variables. The results indicate that most households participating in this study are classified as food secure, and the majority of children under five are neither underweight nor wasted. While a positive link was identified between household income and food security, no significant correlation was observed between income and the nutritional status of children under five, as measured by WAZ or BAZ scores. Additionally, no relationship was found between household food security and the nutritional status of children under five based on WAZ or BAZ assessments.